2013
DOI: 10.5402/2013/140905
|View full text |Cite
|
Sign up to set email alerts
|

Serum NGAL in Critically Ill Children in ICU from a Single Center in Egypt

Abstract: Introduction. The mortality and morbidity associated with acute kidney injury (AKI), unfortunately, remain unacceptably high. We aimed to detect the extent of serum neutrophil gelatinase-associated lipocalin (NGAL) to early detect AKI in critically ill children. Subjects and Methods. This is a case control study. It included 75 subjects that include 15 as controls and 60 critically ill children. Patients were further subdivided according to RIFLE criteria into two other categories: patients who developed AKI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…1 Serum creatinine values in critically ill children group showed no statistically significant difference when compared with controls. 18 These findings agree with Bailey et al who reported that there was a significant difference in serum NGAL between critically ill children and the control group. 19 Kari et al evaluated urinary NGAL in critically ill PICU children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1 Serum creatinine values in critically ill children group showed no statistically significant difference when compared with controls. 18 These findings agree with Bailey et al who reported that there was a significant difference in serum NGAL between critically ill children and the control group. 19 Kari et al evaluated urinary NGAL in critically ill PICU children.…”
Section: Discussionsupporting
confidence: 91%
“…A a cutoff value of 89.5 ng/mL, urinary NGAL showed sensitivity of 84.6%, specificity of 59.6%, positive predictive value of 36.7%, and negative predictive value of 68.4%. 18 Kari et al also demonstrated that urinary NGAL levels were highly predictive of AKI (AUC=0.76, 95% CI 0.61-0.92). The cutoff point with the highest correctly classified proportion was 223 ng/mL, which correctly predict 80.0% patients with AKI, with a corresponding sensitivity of 72.7% and a specificity of 89.9%.…”
Section: Discussionmentioning
confidence: 95%
“…Some biomarkers with high sensitivity and specificity can be used as an efficient tool for the early detection of AKI, which will help prevent the burden of mortality and morbidity in intensive care units [14][15][16]. Neutrophil gelatinase-associated lipocalin (NGAL) has recently been identified as a strong marker in predicting early AKI [17,18]. Several published studies have stated that plasma NGAL level rises earlier than SrCr in AKI [19].…”
Section: Introductionmentioning
confidence: 99%